Arab Spring future challenges: evidence from Egypt. Issue 2 (6th September 2018) - Abdou, Doaa Salman; Zaazou, Zeinab
Abstract : Purpose: This paper aims to shed light on the Egyptian socio-economic and political conditions seven years post the 2011 revolution. Design/methodology/approach: The authors depended on secondary data and information gathered from scholars and from domestic and international institutions as well. Additionally, the authors distributed 390 Likert-scale questionnaires among respondents to test their perceptions regarding the safety, social, political and economic conditions in Egypt seven years post the 2011 revolution. Findings: The research findings confirmed that there was an agreement among participants that the safety conditions in Egypt improved during the past seven years post the 2011 revolution, and there was a general agreement among participants that the political conditions in Egypt became more stable lately. The economic and social cost presents a challenging status to the current decision maker. Practical implications: Finally, authors came up with recommendations aiming to find solutions for certain economic and political problematic issues. The main research limitation is that the representative sample was confined only to the two main governorates in Egypt: Cairo and Giza. Originality/value: Finally, the study is of a value, as it could be considered a road map to policy makers. Moreover, the findings provide a set of policies for governments to undertake tenable actions to accelerate development and economic growth.